Climate change, water management and stakeholder analysis in the Dongjiang River basin in South China - Yang, Liang Emlyn; Chan, Faith Ka Shun; Scheffran, Jürgen (Taylor & Francis, 2016)
This article proposes a systematic analysis of water management and allocation on the scale of a river basin, considering climate impacts and stakeholder networks in the Dongjiang River basin in South China. Specific approaches are integrated to explore various subtopics. Findings indicate a slight increase of precipitation in the basin and strong fluctuations in this century due to climate extremes, which may lead to seasonal or quality-related water shortages. It is highlighted that alternative options for holistic water management are needed in the basin, and participatory water allocation mechanisms and establishment of a basin-wide management framework could be helpful.